Joining of Zirconia Reinforced Metal–Matrix Composites by a Ceramics‐Derived Technology1. Issue 9 (9th March 2015) - Weigelt, Christian; Jahn, Elisabeth; Berek, Harry; Aneziris, Christos G.; Eckner, Ralf; Krüger, Lutz
<x xml:space="preserve">Abstract</x> Metal–matrix composites composed of an austenitic stainless steel and magnesia partially stabilized zirconia were prepared via a powder metallurgical processing route with the ceramics‐derived extrusion at room temperature. Various combinations of the base materials with zirconia volume fractions of 0, 5, and 10% were joined by applying an aqueous paste which forms the joint during thermal processing. The materials were tested under tensile loading at room temperature. The addition of zirconia particles led to a considerable decrease of the plasticity and ultimate tensile strength of the basic compositions. However, the strength of joint specimens was not limited by the bonding strength of the joining zone. Among all material combinations tested, failure occurred in the joining partner with the higher zirconia volume fraction and not at the joint interface. Thus, the strength of sinter‐joined materials based on MMC with 0–10 vol% was limited by the strength of the base materials. The advance of the present sinter‐joining method is the single thermal operation of the composite materials. The formation of a homogeneous bonding zone and the absence of a heat‐affected zone lead to negligible interference with the microstructure and the mechanical properties of the base materials.